Do people make decisions under risk based on ignorance? An empirical test of the priority heuristic against cumulative prospect theory - Glöckner, Andreas; Betsch, Tilmann (Organizational behavior and human decision processes, 2008)
Brandstätter, Gigerenzer, and Hertwig [Brandstätter, E., Gigerenzer, G., & Hertwig, R. (2006). The Priority Heuristic: Making choices without trade-offs. Psychological Review, 113(2), 409–432] put forward the priority heuristic (PH) as a fast and frugal heuristic for decisions under risk. According to the PH, individuals do not make trade-offs between gains and probabilities, as proposed by expected utility models such as cumulative prospect theory (CPT), but use information in a non-compensatory manner and ignore information. We conducted three studies to test the PH empirically by analyzing individual choice patterns, decision times and information search parameters in diagnostic decision tasks. Results on all three dependent variables conflict with the predictions of the PH and can be better explained by the CPT. The predictive accuracy of the PH was high for decision tasks in which the predictions align with the predictions of the CPT but very low for decision tasks in which this was not the case. The findings indicate that earlier results supporting the PH might have been caused by the selection of decision tasks that were not diagnostic for the PH as compared to CPT.